Role of Customary Law to Pornography Through Technology Media - Irfansyah; Nabella Puspa Rani; Vita Amelia; Triono Dul Hakim (Advances in Humanities and Contemporary Studies, 2021)
Factor that can influence pornographic behaviour in adolescents is media that provides information and sexual stimulation. According to data from the Ministry of Communications and Information, at least 30 million children and adolescents in Indonesia are internet users, and digital media is the crucial choice of communication channels used. Pornographic activities that are accessed through technology contribute to the destruction of the nation’s morals. This threat requires preventive and repressive efforts from various legal systems in force in Indonesia, including the customary legal system. Customary law is a guarantee for native people to create a conducive customary environment under customary norms that have been agreed upon. Customary law requires the community to be loyal and loyal to the customary law, so that customary law can grow, develop and bequeathed to its generation. Customary law also contributes to tackling pornography, one of which is by providing customary sanctions.